Glucose Oxidase-dextran Conjugates with Enhanced Stabilities Against Temperature and pH - OGAN, AYŞE (HUMANA PRESS INC, 2010)
Multipoint covalent bonding of glucose oxidase (EC 1.1.3.4) to hydrophilic natural polymer dextran and optimization of procedures to obtain, with enhanced temperature and pH stabilities, were studied. Purified enzyme was conjugated with various molecular weight dextrans (17.5, 75, and 188 kD) in a ratio of 20:1, 10:1, 1:1, 1:5, 1:10, 1:15, and 1:20. After 1 h of incubation at pH 7, the activities of purified enzyme and conjugates were determined at different temperatures (25 degrees C, 30 degrees C, 35 degrees C, 40 degrees C, 50 degrees C, 60 degrees C, 70 degrees C, and 80 degrees C), and the results were evaluated for thermal resistance. Increases in temperature from 25 degrees C to 50 degrees C did not change the activities of the conjugates. The conjugate, which was prepared with 75 kDa dextran in a molar ratio of 1:5, showed the highest thermal resistance and even the activity still remains at 80 degrees C at pH 7.0. This conjugate also displayed activity in a wide pH range (pH 4.0-7.0) at high temperatures. Conjugate, which was synthesized with 75 kDa dextran in a molar ratio of 1:5, appears to be feasible and useful for biotechnological applications.
Keywords: Thermal stabilization; Covalent conjugate; Glucose oxidase; Dextran; Fluorescence; ENZYME; CHROMATOGRAPHY; PURIFICATION; ALDEHYDE; IMMOBILIZATION; INACTIVATION; EXPRESSION; LIPASES